Pemberdayaan Masyarakat Berbasis Martech pada Kelompok Usaha Bersama Pedado di Era Digital: Community Empowerment Based on Martech in the Pedado Joint Business Group in the Digital Era - Abdul Bashir; Waldi Novi Yarsah; Ahmad Syaifullah; Sabam Syahputra Manurung; Nugraha Pratama; Rosada Sintya Dwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This community service program aims to enhance the digital capacity and marketing capabilities of members of the Joint Business Group (KUBE) Pedado through a marketing technology (martech) approach. The program was implemented from June to December 2025 and involved 20 participants through training sessions, workshops, simulations, and intensive mentoring. The materials covered digital content creation, social media optimization, the utilization of WhatsApp Business, and performance analysis using Meta Business Suite. Evaluation was conducted using pre-tests and post-tests, complemented by observations of participants’ digital activities. The results indicate a significant improvement in participants’ competencies. The average score increased from 52.6 to 82.6, representing a 57.03% improvement. Specifically, digital literacy increased by 45.45%, content creation skills by 64.00%, social media management by 63.46%, use of WhatsApp Business by 51.72%, and understanding of digital analytics by 62.50%. In addition, there was an increase in digital engagement, reflected in higher interaction rates and market reach. The program also strengthened business branding and fostered a shift in entrepreneurial mindset toward a growth mindset. Therefore, the martech approach has proven effective in improving the digital capacity and marketing performance of community-based MSMEs and demonstrates strong potential for sustainable replication.